Decentralization and Effective Educational Leadership: Expectation versus Reality - CECEP SOMANTRI (Indonesian Research Journal in Education |IRJE|, 2018)
Decentralization is a management reform that is widely believed to promise a range of benefits in transforming society and the effectiveness of local governance. By 1999, nearly all countries in the world were experimenting with decentralization, at least in policy level. Education is inevitably one of the sectors that has been affected by decentralization. In a devolved education system, schools are given both autonomy and responsibilities in decision-making authority. At school level, those who receive the transferred-authority are mainly principals, and hence, they have broadened-roles and responsibilities. However, research and literature drawn from more than four decades show that a devolved environment urges for accountability that is oftentimes regarded as pressure and dilemma by school leaders and teachers. As a result, there is an urgency to have a systemic solution that acknowledges the important role of principals, clarifies the responsibilities and roles of principal, and develops capacity of principals.